The pragmatic aspect in the interpretation of kinem (Eurasian Journal of Learning and Academic Teaching, 2023)
Pragmatics is a section of semiotics. Studies the features of the use of signs in communication, the relationship of signs to the interpreter. Pragmatic factors include a wide variety of information. This information allows us to establish the meaning of language expressions and utterances in a given situational (pragmatic) context.